(untitled) (Journal of Plant Disease Sciences, 2023)
Pearl millet is infected by many diseases, which cause yield reduction and economic losses to the grower. Among several diseases, blast disease has emerged as a serious one, affecting both forage and grain production of pearl millet. The research work has been carried out at the Center for Crop Improvement, S. D. Agricultural University, S. K. Nagar, during the Kharif seasons of 2018 and 2019. The experiment comprising susceptible cultivars of pearl millet was conducted on varied planting dates (D1: 27th June, D2: 4th July, D3: 11th July, and D4: 18th July) to find out the appropriate date of sowing for management of blast under natural conditions. The minimum disease intensity (63.27%) was observed in the 4th July sown crop, followed by the 11th July sown crop (70.47%). The next treatment in merit was the 27th June sown crop (70.77%). The maximum intensity (72.49%) was recorded in the 18th July sown crop.